Advances in macrofungi : diversity, ecology and biotechnology - Sridhar, K. R. (Boca Raton : CRC Press, 2018)
Advances in Macrofungi: Diversity, Ecology and Biotechnology discusses the diversity and ecology of edible, toxic, medicinal and mycorrhizal macrofungi; the impact of ectomycorrhizal fungi in terrestrial ecosystems, ectomycorrhizal complex in Boreal forests and commercial application of Pseudotsuga in silviculture; the nutritional evaluation and cultivation of edible wild mushrooms; the diversity of novel metabolites of macrofungi useful in food, pharmaceutical and cosmeceutical industries; mushrooms as tool for eco-friendly synthesis of nanoparticles and proteomics of edible and medicinal mushrooms. In addition, it covers experimental designs, methodological approaches, biogeochemical cycles, conceptual/hypothetical models and life history strategies, linking mycorrhizal diversity to plant performance, chemotaxonomy, role of mycorrhizae in forestry and macrofungi in nanotechnology. It provides a valuable resource to graduate, post-graduate and researchers (in botany, microbiology, ecology, biotechnology, forestry, life sciences and environmental sciences) to understand the diversity, ecology, therapeutic value, mutualistic associations and biotechnological potential of macrofungi.
"A science publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Macrofungi; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; HEALTH & FITNESS / Herbal Medications; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General